Influence of Bi2O3 content on structural, optical and radiation shielding properties of transparent Bi2O3-Na2O-TiO2-ZnO-TeO2 glass ceramics - Fong, W. L.; Bashar, KhA.; Baki, S. O.; Karim, M. K. A.; Sayyed, M. I.; Mahdi, M. A.; Goh, B. T. (Elsevier, 2022)
This study aimed to evaluate the thermal, structural, optical and radiation shielding properties of the xBi2O3–5Na2O–5TiO2–10ZnO-(80-x)TeO2 glass ceramics, where x = 5, 8, 10, 12, and 15 mol% using the conventional melt quenching technique while controlled the heat treatment. The thermal properties of the sample glasses, such as glass transition temperature, onset crystallization temperature, and glass stability, were estimated from the differential scanning calorimetry measurements. The glass stability was found to decrease as Bi2O3 content increased. The tendency of crystallization was also found to increase correspondingly which evidenced by the sample glass with a higher percentage of Bi2O3 content has crystallized in a shorter period of heat treatment, lost transparency, and forming multiple crystalline phases correspondingly as shown in the XRD results. The optical band gap decreased as the period of controlled heat treatment prolonged. A low energy band gap indicates the high polarizability of the sample glass due to the high polarizability of non-bridging oxygen. The material discussed here has high relevance to laser, non-linear optics, and optical communication applications. The physical and ionizing shielding features were investigated for current glass samples. The shielding properties were examined within the energy range of 0.015 until 15 MeV. The sample S5 has the optimum shielding features as a result of the addition of Bi2O3. Hence, the composition attributes a new glass system that can be used in various applications such as optical communication applications, radiation dosimeter and photon shielding materials.